2019
DOI: 10.3389/fpsyg.2019.01018
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Attitude Strength in Behavioral Spillover: Attitude Matters—But Not Necessarily as a Moderator

Abstract: Studies on how one behavior affects subsequent behaviors find evidence for two opposite trends: Sometimes a first behavior increases the likelihood of engaging in additional behaviors that contribute to the same goal (positive behavioral spillover), and at other times a first behavior decreases this likelihood (negative spillover). A factor that may explain both patterns is attitude strength. A stronger (more favorable) attitude toward an issue may make the connections between related behaviors more salient an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 107 publications
(183 reference statements)
0
12
1
Order By: Relevance
“…It is postulated that attitude could act as antecedent of behavior [31,32]. Consequently, pedestrians' attitude toward road crossing behavior would be determinant factor for individuals to protect her/him alongside of environmental modifications.…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that attitude could act as antecedent of behavior [31,32]. Consequently, pedestrians' attitude toward road crossing behavior would be determinant factor for individuals to protect her/him alongside of environmental modifications.…”
Section: Discussionmentioning
confidence: 99%
“…All participants who agreed actually performed the task. We view the measure as an indicator of donating time to help an environmental organization, much like donating money to help an environmental organization, which has been used as a measure of PEB in several spillover studies ( Carrico et al, 2018 ; Brügger and Höchli, 2019 ; Eby et al, 2019 ). Additionally, the measure is an extension of previous spillover research that asked participants to hypothetically allocate volunteer time among charities including pro-environmental organizations ( Margetts and Kashima, 2017 ).…”
Section: Studymentioning
confidence: 99%
“…However, players' prosocial intentions did not increase. Other factors such as direct, consistent and stable exposure to the attitude object (in this case, a prosocial game) over time [32] and strength of the attitudinal change felt by the participant [33] may be required to promote improved behavioral intentions. Rusch [34] has also suggested that attitudinal change is more attainable than behavioral change, because although attitudinal change can provide powerful suggestion, any subsequent behavioral change that is not accompanied by a change of identity only increases the chances of reverting to previous norms or status quo.…”
Section: Discussionmentioning
confidence: 99%